2020
DOI: 10.1063/1.5130519
|View full text |Cite
|
Sign up to set email alerts
|

Operating a cesium sputter source in a pulsed mode

Abstract: A scheme is presented for pulsing of a cesium sputter negative ion source by periodically switching on and off the high voltage driving the sputtering process. We demonstrate how the pulsed ion beam can be used in combination with a pulsed laser (6 ns pulse length) that has a 10 Hz repetition rate to study the photodetachment process, where a negative ion is neutralized due to the absorption of a photon. In such experiments, where the ion beam is used only for a small fraction of the time, we show that the pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It has been recently demonstrated that the negative ion beam current from the SNICS source can be enhanced with cathode voltage pulsing [22,23]. For example, in [22] it was reported that the C − and C − 4 beam currents can be enhanced up to 400% by pulsing the cathode voltage in Cs-depleted condition, although the same beam current was obtained with continuous cathode voltage at higher Cs feed rate (oven temperature).…”
Section: Jinst 18 C07002 4 Discussionmentioning
confidence: 96%
“…It has been recently demonstrated that the negative ion beam current from the SNICS source can be enhanced with cathode voltage pulsing [22,23]. For example, in [22] it was reported that the C − and C − 4 beam currents can be enhanced up to 400% by pulsing the cathode voltage in Cs-depleted condition, although the same beam current was obtained with continuous cathode voltage at higher Cs feed rate (oven temperature).…”
Section: Jinst 18 C07002 4 Discussionmentioning
confidence: 96%
“…The role of Cs coverage is best illustrated by the experiments with the high power laser using varying pulse repetition rates and pulse lengths, demonstrating that with sufficient laser power and inappropriate Cs coverage, the long-term effect of the laser can be adverse. It has been observed 18 that operating the SNICS source in pulsed mode can sometimes (under certain operating conditions) lead to enhanced beam currents although systematic trends covering various ion species were not found. It is plausible that, similar to photo-assisted negative ion production with the laser exposure, the performance of the SNICS ion source in pulsed mode is sensitive to variations of the cathode Cs coverage.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the possible role of photon absorption in the electron capture process has not hitherto been studied, whereas Blahins et al have recently used a laser to study photodetachment with a cesium sputter source. 18…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…Finally, it could be argued that photon absorption might increase the negative ion yield by allowing photoelectrons to overcome the surface potential barrier and become bound to the affinity level of the ejected atom, thus supplementing the described electron capture by tunneling. To our knowledge the possible role of photon absorption in the electron capture process has not hitherto been studied whereas Blahins et al have recently used a laser to study photodetachment with a cesium sputter source 17 .…”
Section: A Surface Production Of Negative Ions By Cesium Sputteringmentioning
confidence: 99%